Methodology for analysing Multi-Airport System Capacity: SBPL MMMX System Case - Mujica Mota, Miguel (2019)
The following paper presents a simulation-based methodology for analysing the potential operational capacity of a multiairport system. The case presented is the one of the region of Mexico City composed by Santa Lucia Airport and Mexico City. The study is composed of several modules that compose the multi-airport system: airport(s) and airspace. Together they form an integrated model in which the different elements interact for revealing the capacity potential of the region of Mexico city. Then an experimental design is developed under different time horizons which allow identifying the problems that will arise once the traffic increases in the coming years. It will allow us to identify the limitations, problems and potential of the region of Mexico city. This research is original research in which for the first time proposes a methodology for identifying the capacity of a system composed of different airports which have the common objective of serving a geographical region.